Diversity in Hydrogen-rich Envelope Mass of Type II Supernovae. II. SN 2023ixf as Explosion of Partially Stripped Intermediate Massive Star - Fang, Qiliang; Moriya, Takashi J.; Ferrari, Lucía; Maeda, Keiichi; Folatelli, Gaston; Ertini, Keila Y.; Kuncarayakti, Hanindyo; Andrews, Jennifer E.; Matsumoto, Tatsuya (IOP Publishing Ltd, 2025)
SN 2023ixf is one of the most well-observed core-collapse supernovae in recent decades, yet there is inconsistency in the inferred zero-age main-sequence (ZAMS) mass M- ZAMS of its progenitor. Direct observations of the pre-supernova (SN) red supergiant (RSG) estimate M ZAMS spanning widely from 11 to 18 M- circle dot. Additional constraints, including the host environment and the pulsation of its progenitor RSG, suggest a massive progenitor with M- ZAMS > 17 M- circle dot. However, the analysis of the SN properties, from light-curve modeling to late-phase spectroscopy, favors a relatively low-mass scenario (M- ZAMS < 15 M (circle dot)). In this work, we conduct a systematic analysis of SN 2023ixf, from the RSG progenitor, plateau phase light curve to late-phase spectroscopy. Using MESA+STELLA to simulate the RSG progenitor and their explosions, we find that a range of the RSG models having M (ZAMS) that vary from 12 to 17.5 M- circle dot can reproduce its multiband light curves if the hydrogen-rich envelope mass and the explosion energy are allowed to vary. Using late-phase spectroscopy as an independent measurement, the oxygen line [O i] indicates an intermediate-massive progenitor (M- ZAMS similar to 16.0 M (circle dot)). By incorporating the velocity structure derived from the light-curve modeling into an axisymmetric model, we generated [O i] line profiles that are consistent with the [O i] line observed in late-phase spectroscopy of SN 2023ixf. Bringing these analyses together, we conclude that SN 2023ixf is the aspherical explosion of an intermediate-massive star (M- ZAMS = 15-16 M (circle dot)), with the hydrogen envelope being stripped to 4-5 M (circle dot) prior to its explosion.